Restoration of degraded subtropical thickets in the Baviaanskloof Megareserve, South Africa: the role of carbon stocks and Portulacaria afra survivorship - Powell, Michael John (Rhodes University, Faculty of Science, Department of Environmental Science, 2009)
The semi-arid forms of subtropical thicket in the Eastern and Western Cape have been heavily degraded through unsustainable pastoralism over the last century or more. The degraded areas exhibit a significant loss of above-ground and belowground carbon stocks, and consequently provide an opportunity for restoration through the formal and informal carbon markets. A prerequisite for the attainment of carbon credits is to ensure sound carbon stock baselines prior to effecting restoration. I report on the carbon stocks (including sub-pools) for a number of intact subtropical thicket types, as well as the differentials between the intact and degraded states (including the sub-pools). Total carbon stocks (TCS in t C haâ »Â¹) for intact vegetation (to a soil depth 0"“25 cm), ranged from 87.73Â±6.51 to 70.64Â±17.24. For degraded vegetation (including old lands), TCS (t C haâ »Â¹) ranged from 34.05Â±3.61 to 21.03Â±2.70. For all vegetation types, the differentials in TCS along the degradation gradient (0"“25 cm) are highly significant and strengthen the possibility for carbon credit financing to catalyse the restoration of the degraded semi-arid subtropical thickets. This study has shown a mean loss of 57.23 t C haâ »Â¹ in Baviaanskloof spekboom thickets, when measured to a soil depth of 25 cm. Portulacaria afra is a key species within the semi-arid subtropical thickets, being a canopy dominant and a driver of soil nutrient status, but has been largely lost from the degraded landscapes. Degraded semi-arid subtropical thicket vegetation lacks regeneration via seedling recruitment; restoration therefore requires the manual replanting of P. afra using cut truncheons. Survivorship trials were undertaken infield in 2005 to establish restoration protocols for P. afra, with survivorship being recorded in 2006 and 2008. Overall survivorship for all treatments was found to be 43.2Â±2.8% in 2006, dropping to 35.8Â±2.7% in 2008. Planting posture (flat or upright) showed the most significant results of all the factors tested in 2006 and 2008. Micro-damming also influenced survivorship in that micro-damming was associated with marginally higher survivorship (47.4 Â±2.0% with damming vs. 39.1Â±1.5% without damming in 2006, and 39.3Â±1.9% vs. 32.3Â±1.5% in 2008). Higher planting density only showed a significant positive impact on survivorship in 2008. Neither stem diameter nor clumping significantly affected degree of survival. A key finding in the study has been the non-static nature of P. afra truncheon survivorship, even after being well established (three years since planting). The results from the study will guide the restoration protocols for the restoration of degraded subtropical thickets, where P. afra requires replanting.
Keywords: Portulacaria afra -- South Africa -- Eastern Cape; Portulacaceae -- South Africa -- Eastern Cape; Biodiversity conservation -- South Africa -- Eastern Cape; Plant conservation -- South Africa -- Eastern Cape; Shrubs -- South Africa -- Eastern Cape; Succulent plants -- South Africa -- Eastern Cape; Baviaanskloof (South Africa)